Fauna and Checklist of Mosquitoes (Diptera: Culicidae) of East Azerbaijan Province, Northwestern Iran - MR Abai; S Azari-Hamidian; H Ladonni; M Hakimi; K Mashhadi-Esmail; K Sheikhzadeh; A Kousha; H Vatandoost (Tehran University of Medical Sciences, 2007)
In order to study the mosquito (Diptera: Culicidae) fauna of East Azerbaijan Province, some samplings were carried out by dipping method for the larvae and hand catch, night biting catch, total catch, and shelter pit collection as well as using window trap for the adults during June, July, and August 2004 plus July and August 2005. In total, 1305 adult mosquitoes and 603 larvae were collected. Seven genera and 15 species were identified in the prov¬ince including; Anopheles claviger, An. hyrcanus, An. maculipennis s.l., An. pseudopictus, An. sacharovi, An. superpictus, Aedes vexans, Coquillettidia richiardii, Cx. pipiens, Cx. theileri, Cx. tritaeniorhynchus, Culiseta longiareolata, Cs. subo¬chrea, Ochlerotatus caspius s.l., and Uranotaenia unguiculata. An. maculipennis complex, Cx. pipiens, and Cx. theileri were the most prevalent and widely dis¬tributed species. An. pseudopictus, Ae. vexans, and Cq. richiardii are reported for the first time in East Azerbaijan Province and a checklist for the mosquitoes of the province is also presented. Among the mosquitoes of the province, there are many potential vectors of human and domesticated animal pathogens that their ecology needs to be studied extensively.